Thermally nonreactive and chemically reactive metal-oxide-nanowire transistor covered with aerogel-microsphere-thin-film-based selective filter. (5th September 2018) - Lim, Taekyung; Kang, Youngsoo; Jeong, Sang-Mi; Ju, Sanghyun
Abstract: The development of a passivation method for an oxide-based chemical sensor that operates only on certain chemical elements without being affected by the external environmental conditions, especially changing ambient temperature, is a critical factor because the long-term stable and reliable operation of the sensor could deteriorate without a passivation layer. In this study, an aerogel microsphere thin film as a passivation layer was applied to the top of a SnO2 -nanowire-based chemical sensor for ensuring stable operation under external heat and liquid exposure conditions, providing low thermal conductivity (∼0.02 W m −1  · K) and hydrophobic (contact angle of ∼145°) characteristics. Externally generated heat and liquid-based-chemical/water were blocked by the aerogel microsphere thin film, and only the chemical vapor passed through the mesopores of the aerogel microsphere thin film. By using this selective permeation function, the fabricated sensor was able to accurately read the chemical concentration in the water–liquid chemical mixture without being affected by the various external heat and liquid exposure conditions. The rise/decay times of the reaction with the water–nitric acid mixture and the water–methanol mixture derived from the sensing characteristics were ∼0.9/0.3 s (nitric acid) ∼0.6/0.3 s (methanol), respectively.